Designing nutritious and sustainable diets : Investigating the impact of plant-based alternatives on gut health in healthy individuals - de Mel, Rumathi ; 0009-0002-7588-5539; Purhagen, Jeanette K ; 0000-0002-2891-1098; Sjöberg, Klas ; 0000-0002-8700-9141; Håkansson, Åsa ; 0000-0001-7584-5540 (39th EFFoST International Conference, Porto, Portugal, 2025-11-17 - 2025-11-19, 2025)
Aim: This study evaluates the health effects of plant-based dairy alternatives in healthy individuals and those with Inflammatory Bowel Disease (IBD). Specifically, it investigates whether replacing one daily meal with a plant-based alternative has a positive impact on intestinal microbiota composition and gut health. It also investigates whether the effect of probiotic bacteria in yogurt depends on the food matrix (plant-based vs. dairy-based). Method: An open, prospective 4-week intervention trial is conducted with 60 healthy individuals and 60 IBD patients, each consuming 200 g/day of either plant-based or dairy-based commercially available yogurt, ideally replacing one meal (e.g., breakfast or snack). Each participant serves as their own control. Probiotic products, other yogurts, and fermented foods are restricted during the study period. Outcomes include disease phenotyping and disease activity assessment through questionnaires and laboratory data. Gut microbiota changes are analysed from faecal samples using Illumina MiSeq sequencing and processed through the QIIME2™ pipeline. The study is a collaboration between the Department of Process and Life Science Engineering, LTH, Lund University, and the Department of Gastroenterology, Skåne University Hospital. Ethical approval has been granted by the Swedish Ethical Review Authority (DNR: 2024-05870-01). Results: Preliminary results (n=10) show a 16.7% decrease in Firmicutes and a 19% increase in Bacteroidetes in the plant-based group. The dairy-based group showed a 15.5% decrease in Firmicutes and a 27.5% increase in Bacteroidetes. At the genus level, Bacteroides increased in both groups, while Faecalibacterium and Prevotella showed divergent trends. Beta diversity also differed between groups. While statistical significance cannot yet be assessed, early trends suggest that plant-based alternatives influence gut microbiota. Ongoing analyses include dietary fibre, phytic acid, and microbial composition. Conclusion: As plant-based alternatives become increasingly popular, it is crucial to understand their health effects, particularly for individuals with chronic conditions such as IBD, as well as for healthy individuals. This study aims to provide valuable insights into the role of gut microbiota in mitigating potential risks and enhancing the benefits of plant-based alternatives, with important implications for gut health.